Ecosystem responses to anthropogenic and natural forcing over the last 100 years in the coastal areas of the East China Sea. (May 2016) - Xing, Lei; Zhao, Meixun; Zhang, Ting; Yu, Meng; Duan, Shanshan; Zhang, Rongping; Huh, Chih-An; Liao, Wen-Hsuan; Feng, Xuwen
Ecosystem changes of the coastal areas of the East China Sea (ECS) during the past 30 years have been characterized by increased productivity and increased occurrences of dinoflagellate red tides; both were commonly attributed to be caused by anthropogenic input of nutrients. However, climate-driven regime shifts were found in the Pacific, but they have not been observed in the ECS owing to the lack of continuous high resolution data. Hence, it is still a challenge to distinguish the influences of anthropogenic activities and climate changes on ECS shelf ecosystem. We compare phytoplankton biomarker (brassicasterol, dinosterol, and alkenones) data of five box cores from the coastal area of the ECS, which afford phytoplankton productivity and community structure records at decadal-scale resolution for the last 100 years. Phytoplankton productivity in all cores increased during the past 50 years, but community structure changes showed different trends. Relative diatom contribution revealed a decreasing trend during the past ca. 50 years in cores DH5-1 and CJ43 collected near the Changjiang Estuary, which were likely caused by increased N/Si and N/P ratios, providing conditions more favorable for dinoflagellates growth. In contrast, the relative diatom contribution increased in cores 32, 34, and DH6-3 further away and south of the Changjiang Estuary, suggesting limited influence of the Changjiang water. Instead, diatom increasing trend is likely caused by increased supply of phosphorus and silicate, as a result of larger Kuroshio intrusion flux and the corresponding strengthened coastal upwelling. Therefore, both anthropogenic activities and climate-driven coastal upwelling have contributed to increased productivities, but these two forcing mechanisms have resulted in contrasting community structure changes at different sites in the coastal area of the ECS.